Exergy Study of Steam Flash Cycle & Kalina Cycle at Waste Heat Recovery Power Generation Operation System - Arfidian Rachman; Benny Arianto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
Waste Heat from cement kiln factories has begun developed to power generation in the world. Waste Heat Recovery Power Generation (WHRPG) is the one of power generation with use hot gas from cement kiln to increase water temperature in After Quenching Cooler (AQC) & Preheater (SP) Boiler, and change water into superheated steam stage. Superheated Steam will delivery in to turbine and drive the generator. The quality of hot gasses will affect the turbine work and power generator. The temperature of hot gasses frequently at below 340°C. It will cause turbine not work in optimally condition. This research done for study using ammonia – water on kalina cycle at WHRPG to resolve the problem in WHRPG. From this study found that value of total exergy destruction at Steam Flash Cycle is 19,97 MW with power generator 7,011 MW. While at kalina cycle, total exergy destruction the kalina cycle is 18,33 MW with power generator at 8,459 MW.